2015
DOI: 10.1044/2014_ajslp-14-0089
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Psychosocial Factors and Quality of Life for Adults Who Stutter

Abstract: Increased self-esteem/self-efficacy and social support from family relates to improved quality of life in adults who stutter, independent of stuttering severity. Treatments that increase feelings of self-esteem/self-efficacy and strengthen social support from the family should be considered for individuals who struggle to cope with stuttering in order to enhance their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 65 publications
(54 reference statements)
1
28
0
7
Order By: Relevance
“…Furthermore, the perceived social support levels among mothers were found to be moderate. Previous studies have reported that variables such as self-efficacy, social support and healthy social functioning contribute to the resilience of stuttering adults (15) and that social support positively affects their sense of belonging and well-being (18) . Moreover, a study conducted using a qualitative methodology reported that families expected support from professionals, as their knowledge is limited (9) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the perceived social support levels among mothers were found to be moderate. Previous studies have reported that variables such as self-efficacy, social support and healthy social functioning contribute to the resilience of stuttering adults (15) and that social support positively affects their sense of belonging and well-being (18) . Moreover, a study conducted using a qualitative methodology reported that families expected support from professionals, as their knowledge is limited (9) .…”
Section: Discussionmentioning
confidence: 99%
“…They also mentioned that social support is beneficial because it augments a sense of belonging and well-being. However, the social support levels of participants are smaller than those of controls (17) , and the social support provided by family members significantly affects the quality of life of PWS (18) . Consequently, the importance of the role played by the family in the therapy process and in enhancing communication with children about stuttering in order to increase the social support presented by family members is highlighted (18) .…”
Section: Studies On Resilience Social Support and Trait Anxiety Levelsmentioning
confidence: 90%
See 1 more Smart Citation
“…The postlexical phase of word production encompasses several proposed processes and a disruption of any of them could lead to overt anomia after sIS, e.g., loss of the phonological trace or a failure of sensorimotor mapping, phonological assembly, phonetic encoding, or articulatory planning (Goldrick & Rapp, 2007; Indefrey & Levelt, 2004; Indefrey, 2011; Walker & Hickok, 2015). The last of these, a failure of articulatory motor planning, often falls under a diagnosis of verbal apraxia or acquired apraxia of speech (Duffy et al, 2015; Strand, Duffy, Clark, & Josephs, 2014; Whiteside, Dyson, Cowell, & Varley, 2015). Individuals with anomia who report frequent sIS should perform poorly on tasks that rely heavily on these output processing skills, such as repetition or oral reading.…”
Section: Introductionmentioning
confidence: 99%
“…Stuttering is a multidimensional, neurodevelopmental communication disorder (A. Smith & Weber, 2017) that can deeply impact psychosocial outcomes for affected individuals (Beilby, 2014;Beilby, Byrnes, & Yaruss, 2012b;Boyle, 2015b;Briley, O'brien, & Ellis, 2019;Craig, Blumgart, & Tran, 2009;Erickson & Block, 2013;Yaruss & Quesal, 2006). Stuttering is characterized by an atypical frequency of stuttering-like disfluencies that interfere with the forward flow of speech including part-word repetitions (e.g., "a-a-and"), single-syllable word repetitions (e.g., "and-and"), prolongations (e.g., "aaaaand"), blocks (e.g., "---and"), and broken words (e.g., "o---pen") .…”
Section: Chapter 1: Introductionmentioning
confidence: 99%